2017
DOI: 10.18662/lumenss.2017.0602.02
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Supervision in Social Work

Abstract: Abstract:The difficulties of working in the social work field, the unexpected situations which the professionals may face, the frequent ethical dilemmas, the emotional hardships request the need of supervision for the social workers in order to achieve a better performance. From a theoretical point of view, the supervision is a solution that can bring support, competence, education, information, orientation, which will provide a good development for the professional workflow. From a practical point of view, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Supervision is a critical factor in the psychological health of social workers (Mak, 2013) and can decrease STS (Quin, 2017). Other studies have reported that social workers often do not receive supervision, due to reasons of employment mentality and lack of financial resources (Voicu, 2017). It is also disturbing that many social workers who did receive supervision found it unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervision is a critical factor in the psychological health of social workers (Mak, 2013) and can decrease STS (Quin, 2017). Other studies have reported that social workers often do not receive supervision, due to reasons of employment mentality and lack of financial resources (Voicu, 2017). It is also disturbing that many social workers who did receive supervision found it unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…External supervision is designed to be distinct from managerial supervision, and is intended to offers a safe space for highly stressed practitioners that is free from power dynamics within their organizations (Beddoe, 2021). Interorganizational supervision tends to be more task-focused and involves higher levels of tension between supervisors and social workers than supervision provided by external sources, while external supervision tends to be more focused on the social workers’ emotions and development and involves less tension than supervision provided by interorganizational sources (Voicu, 2017).…”
Section: Discussionmentioning
confidence: 99%